Millions in poverty grip - Varma, S. C. (New Delhi, 1984)
The 'right to work' is en shrined in India's constitu tion and in the context of the burgeoning unemployment in the villages, the rural works programme brings succour to the millions in the grip of acute poverty.
Keywords: Rural development